Description of Eruption of Permanent Lower Central Incisors in Stunted Children at Koto Balingka West Pasaman Elementary School - Intan B. E. Mahata; Sri P. Utami; Athifa Trisa (Universitas Sam Ratulangi, 2024)
Abstract: Stunting is a linear growth disorder that is not appropriate for the child's age due to malnutrition. Malnutrition in stunted children can affect bone growth. The process of inhibited bone growth will affect the process of maturation of the periodontal bones that support the teeth being hampered so that children can experience delays in tooth eruption. This study aimed to describe the eruption of the permanent lower central incisors in stunted children at Sekolah Dasar (elementary school) Koto Balingka West Pasaman. This was a quantitative-descriptive-observational study with a case control design. Samples obtained by using purposive sampling technique were 68 children consisting of 34 (50%) stunted children and 34 (50%) normal children aged 6-7 years in the working area of the Parit Koto Balingka Health Center. Univariate analysis was presented in the form of frequency and percentage distributions. The results showed that among stunted children, 22 (64.7%) had not erupted permanent lower central incisors meanwhile 12 (35.3%) children did. Moreover, among normal children, 6 (17.6%) had not erupted permanent lower central incisors meanwhile 28 (82.4%) did. In conclusion, most children aged 6-7 years with stunting have not yet had erupted permanent lower central incisors, meanwhile most children with normal nutritional status have erupted permanent lower central incisors, with a mean age of eruption at 7 years. Keywords: stunting; tooth eruption; permanent lower central incisor; malnutrition